The Politics of Gun Control in the United States: A Historical Perspective on the Second Amendment - Rønnedal, Vibeke Sofie Sandager (Leviathan: Interdisciplinary Journal in English, 2019)
The discussion of the right to keep and bear arms has been a growing issue in American society during the past two decades. This article examines the origin of the right and whether it is still relevant in contemporary American society. It is found that the Second Amendment was written for two main reasons: to protect the people of the frontier from wildlife and foreign as well as native enemies, and to ensure the citizen militia being armed and ready to fight for a country with a deep-rooted mistrust of a standing army and a strongly centralized government. As neither of these reasons have applied to American society for at least the past century, it is concluded that American society has changed immensely since the Second Amendment was ratified in 1791, and that the original purpose of the right to keep and bear arms thus has been outdated long ago.